Foliar silicate application improves the tolerance of celery grown under heat stress conditions - Fadl Abdelhamid HASHEM; Rasha M. EL-MORSHEDY; Tarek M. YOUNIS; Mohamed A. A. ABDRABBO (Acta Agriculturae Slovenica)
Temperature rise is one of the most challenging climate change impacts that increase the intensity of heat stress. In this investigated the production of celery (Apium graveolens var. rapaceum F1 hybrid)) was tested during the late season. The experiment was carried out during the two successive summer seasons of 2019 and 2020 in Giza Governorate, Egypt. The experimental design is a split-plot, the main plots consist of three low tunnel cover treatments, and three spray treatments with three replicates in sub-main plots. Results showed that the use of white net cover gave the highest vegetative growth and yield followed by the black net. Values of plant yield were 951, 765, and 660 g/plant for white, black and without cover, respectively, in the first season. The foliar application of 3 mM of potassium silicate produced the highest vegetative growth and yield compared to the control treatment. Referring to the effect of spray foliar application of potassium silicate on yield 1.5 mM (S1), 3 mM (S2), and control were 892, 795, and 689 g/plant in the first season, respectively. The best combination that delivered the highest vegetative growth and yield was a cover low tunnel with a white net combined with S2 foliar application.